Hazards for women and children in rural settings (2015)
Objectives a) To identify possible risk factors associated with rural accidents in women, b) to describe women’s knowledge about zoonosis, c) to describe women’s risk perception about farming, d) to describe mother´s risk perception about children’s activities in rural settings, e) to estimate the initial age of exposure to the rural setting and its dangers, and f) to identify possible risk factors associated with rural accidents in children.Materials and Methods: Cross-sectional design. Women with children that live in the countryside were surveyed (n=24). Structured questionnaire. Statistical analyses: χ2, Student’s t-test, Pearson’s correlation coefficient and logistic regression.Results Many women had suffered an accident in the countryside (65.6 %). Farm worker usually did not use personal protective equipment (PPE). Hearing protection, gloves, and safety goggles were rarely used. Working women showed a high risk perception for urban driving, the handling of agrochemicals, and driving on main roads (85.7 %, 70 % and 66.7 %). There was no significant association between risk perception and PPE use. Most mothers (87.5 %) thought that was good for children to learn how to perform farm chores starting at a young age. Children started to drive a tractors at 9 years of age; 12.23 years on average. More than 7 % of the children (7.14 %) have suffered an accident on the farm. The most frequent accidents were being trapped in machinery (60 %). No association was found between the independent variables and the dependent variable;  farm-related accidents in children (p0.2).Conclusions Risk communication is necessary to inform people involved and to reduce exposure.